Two new hoverfly species of the Merodon desuturinus lineage (Diptera: Syrphidae: Merodontini) - Laura Likov; Ante Vujić; Snežana Radenković; Ljiljana Šašić Zorić; Mihajla Djan; Kurt Jordaens; Sonja Mudri-Stojnić (European Journal of Taxonomy)
The hoverfly genus Merodon Meigen, 1803 (Diptera: Syrphidae) comprises five monophyletic lineages. Here, we describe two new species of the murorum species group and melanocerus species group from the desuturinus lineage. One species, Merodon spinolobus Vujić, Radenković & Likov sp. nov., belongs to the Afrotropical melanocerus species group, and is recorded from the Republic of South Africa. The other species, M. sublustris Likov, Vujić & Radenković sp. nov., is recorded from Iran and belongs to the Palaearctic murorum species group. New species are recognized and described based on morphology and molecular data (3' and 5' COI regions). Additionally, the identification key for the desuturinus lineage is updated and distribution maps for the two new species are provided. Finally, the first distribution data for Merodon cabanerensis Marcos-García, Vujić & Mengual, 2007 (of the murorum species group) from outside of Europe (Morocco) is reported.